2017
DOI: 10.1177/0003489417691300
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed Learning in Otolaryngology Residents’ Preparation for Surgical Cases

Abstract: Otolaryngology residents do not consistently rate their case preparation as effective or efficient. While there appears to be progress in self-directed learning throughout residency, room for improvement remains, with potential avenues for such improvement explored here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Residents report that the amount of time is a primary limitation, and convenience the predominant factor, influencing resource selection. 18 Our survey similarly revealed the variety of resources utilized by residents (Table II). To facilitate the learning process, weekly readings are carefully screened to serve as the best possible resources.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Residents report that the amount of time is a primary limitation, and convenience the predominant factor, influencing resource selection. 18 Our survey similarly revealed the variety of resources utilized by residents (Table II). To facilitate the learning process, weekly readings are carefully screened to serve as the best possible resources.…”
Section: Discussionmentioning
confidence: 76%
“…This can pose a challenge, as residents typically use a variety of sources for preparation for their clinical duties and exams. Residents report that the amount of time is a primary limitation, and convenience the predominant factor, influencing resource selection . Our survey similarly revealed the variety of resources utilized by residents (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…A small pilot study by Poon et al [2] showed the value of otologic surgical videos posted to the YouTube platform for resident education with positive feedback from residents [2]. YouTube is widely available and one study found that as many as 64% of medical students and surgical residents use it in preparation for surgery [3] and another study showed 46% of otolaryngology residents reported using online videos [4].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Hard-copy textbooks have historically been the gold standard; however, electronic media continues to grow with the newer generation of medical professionals. [3][4][5] Smartphone, tablet, and web-based presentation of question banks, readings, and clinical vignettes have been shown to be helpful in delivering educational content to trainees. [6][7][8][9] For example, Hsueh et al recently published improvement in otolaryngology OTE performance for junior residents when using a mobile app platform that allowed primary literature resource sharing and associated multiple-choice questions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several learning techniques and media by which residents learn. Hard‐copy textbooks have historically been the gold standard; however, electronic media continues to grow with the newer generation of medical professionals . Smartphone, tablet, and web‐based presentation of question banks, readings, and clinical vignettes have been shown to be helpful in delivering educational content to trainees .…”
Section: Introductionmentioning
confidence: 99%